Pseudoescópula em Ischnothele annulata (Araneae, Mygalomorphae): avaliando estrutura e funcionalidade na comunicação sexual - Jurgilas, Juliana Paneczko [UNESP] (2019)
Spiders are generally solitary, aggressive, potential cannibal predators, and have poor visual acuity. These features may have favored a strong selection for long-distance communication, such as chemical and/or vibratory signaling. The pheromone usage is an example of signal used during intersexual communication and have been chemically identified in eleven araneomorph species. To the emission of the pheromones, females can use their cuticle or web, and for the perception of these substances, araneomorph males use chemosensory setae located in the dorsal side of the pedipalps. In mygalomorphs, it was reported the presence of a chemosensory setae in an Idiops pylorus male, identified by Scanning Electron Microscopy micrographies. Besides that, recently it was reported a tarsal setae exclusive of mygalomorph males, that have been considered a chemosensory setae because of it’s similarity with the one’s found in Idiops pylorus, and even with the ones found in araneomorphs, despite the contrast in disposition of the setae between the infraorders. They can be arranged densely on tarsus, similar to those setae found in the scopula (and in this case, named pseudoscopula), or be sparsely distributed on ventral tarsus among other setae types. These male setae also differ from other chemosensory ones that are widespread in both males and females of mygalomorph spiders In the present study, the pseudoscopula of a mygalomorph representative, Ischnothele annulata, was investigated through bioassays and transmission electron microscopy. The results indicate that the males identify the conspecific females by chemical signals present in the female silk (contact recognition), and that they do not use long range (volatile) signals to find a mate. The pseudoscopula setae seems to be accountable for the recognition, since the obstruction of the setae prevent males to react to the silk, failing to perform typical courtship when in contact with female’s web. The transmission electronic microscopy analysis of the pseudoscopula seems to indicate a patter similar to those found in chemosensory setae of other group of spiders.